Time in range following flash glucose monitoring: Relationship with glycaemic control, diabetes‐related distress and resource utilisation in the Association of British Clinical Diabetologists national audit. Issue 11 (4th September 2022) - Deshmukh, Harshal; Wilmot, Emma; Pieri, Beatrice; Choudhary, Pratik; Shah, Najeeb; Gregory, Robert; Kilvert, Anne; Lumb, Alistair; Christian, Peter; Barnes, Dennis; Patmore, Jane; Walton, Chris; et al.
Abstract: Aims: The aim of this study was to understand the relationship between time in range (TIR) achieved using the isCGM with changes in glycaemic control, diabetes‐related distress (DRD) and resource utilisation in people living with diabetes. Methods: Clinicians from 106 National Health System (NHS) UK hospitals submitted isCGM user baseline and follow‐up data in a web‐based tool held within the UK NHS network. Linear regression analysis was used to identify the relationship between follow‐up glucose TIR (3.9–10 mmol/L) categories (TIR% 50–70 and TIR% >70) with change in haemoglobin A1c (HbA1c), DRD and Gold score (measure of hypoglycaemia unawareness, where a score ≥4 suggests impaired awareness of hypoglycaemia). Results: Of 16, 427 participants, 1241 had TIR follow‐up data available. In this cohort, the mean TIR was 44.8% (±22.5). With the use of isCGM, at 7.9 months mean follow‐up, improvements were observed in HbA1c (−6.9 [13.5] mmol/mol, p  < 0.001), Gold score (−0.35 [1.5], p  < 0.001) and Diabetes Distress Screening (−0.73 [1.23], p  < 0.001). In the regression analysis restricted to people living with type 1 diabetes, TIR% 50–70 was associated with a −8.9 mmol/mol (±0.6, p  < 0.001) reduction in HbA1c; TIR% >70 with a −14 mmol/mol (±0.8, p  < 0.001) reduction in HbA1c. Incremental improvement in TIR% was also associated with significant improvements in Gold score and DRD. TIR% >70 was associated with no hospital admissions due to hypoglycaemia, hyperglycaemia/diabetic ketoacidosis, and a 60% reduction in the paramedic callouts and 77% reduction in the incidence of severe hypoglycaemia. Conclusion: In a large cohort of UK isCGM users, we demonstrate a significant association of higher TIR% with improvement in HbA1c, hypoglycaemia awareness, DRD and resource utilisation.